Puccini's Turandot : The End of the Great Tradition - Ashbrook, William, 1922-2009; Powers, Harold (Book collections on Project MUSE., 1991)
Unfinished at Puccini's death in 1924, Turandot was not only his most ambitious work, but it became the last Italian opera to enter the international repertory. In this colorful study two renowned music scholars demonstrate that this work, despite the modern climate in which it was written, was a fitting finale for the centuries-old Great Tradition of Italian opera. Here they provide concrete instances of how a listener might encounter the dramatic and musical structures of Turandot in light of the Italian melodramma, and firmly establish Puccini's last work within the tradition of Rossini, B.